2017
DOI: 10.1002/jcb.26165
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in CRISPR‐Cas9 Genome Editing Technology for Biological and Biomedical Investigations

Abstract: The Type II CRISPR-Cas9 is a simple, efficient, and versatile technology for targeted genome editing in a wide range of organisms and cell types. It continues to gain more scientific interest and has established itself as an extremely powerful technology within our synthetic biology toolkit. It works upon a targeted site and generates a double strand breaks that become repaired by either the NHEJ or the HDR pathway, modifying or permanently replacing the genomic target sequences of interest. These can include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(32 citation statements)
references
References 164 publications
(229 reference statements)
0
29
0
Order By: Relevance
“…These hard-to-modify cells would highly benefit from new delivery methods. Consequently, we investigated the potential of 6His-CM18-PTD4 to deliver CRISPR-Cas9 and -Cpf1 RNPs to human T-cell-derived Jurkat and primary NK cells [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…These hard-to-modify cells would highly benefit from new delivery methods. Consequently, we investigated the potential of 6His-CM18-PTD4 to deliver CRISPR-Cas9 and -Cpf1 RNPs to human T-cell-derived Jurkat and primary NK cells [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…These are adaptive immune systems native to bacteria and archaea and can be used for sequence-specific killing of target bacterial strains ( 241 ). It works on a selective site and creates a double stranded nick in the DNA, modifying or permanently replacing the target sequence ( 242 ). Few other studies have reported the successful application of CRISPR-Cas in managing antibiotic resistance and reversing the selection pressure ( 243 , 244 ).…”
Section: Crispr-casmentioning
confidence: 99%
“…The DNA carries CRISPR, a DNA-editing technology offer that cuts away the antibiotic-resistant genes. Recent developments in CRISPR-Cas genome editing technology and its potential application in food bacteria has been recently reviewed elsewhere ( 242 , 246 ). CRISPR-Cas technology can have potential application in controlling AMR at dairy farms, through application of developed product, spray, or liquid, etc., in dairy farm envirnonment, dairy personnel hands, etc.…”
Section: Crispr-casmentioning
confidence: 99%
“…Recent breakthroughs in targeted genome engineering by CRISPR-Cas9 (Jinek et al, 2012 , 2013 ; Mali et al, 2013 ; Singh et al, 2017 , 2018 ) has opened new avenues for genome editing and regulation in a wide range of organisms and cell types. In this light, enabling the use of CRISPR for the modification of bacterial genomes (Jiang et al, 2013 ) has opened the way toward the development of sequence-specific CRISPR-based antimicrobials (Beisel et al, 2014 ; Bikard et al, 2014 ; Bikard and Barrangou, 2017 ).…”
mentioning
confidence: 99%